Professional Training and Supervised Practice in the Field of Social Work in Brazil - Ghiraldelli, Reginaldo (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
The article, based on a theoretical reflection and also on academic experience with the supervision of practices, aims to contribute to the aspect of training in the field of Social Work in Brazil. Emphasis is made on supervised practice in a context marked by a deep political and economic crisis, that provokes serious attacks, threats and budget cuts in public higher education and, at the same time, through neoliberal measures, encourages the proliferation of private and distance education. This context, characterized by the resurgence of conservatism, gives rise to challenges to Social Work, in terms of the defense of a high quality, critical, secular and public training project in Brazil. Among the forms and strategies of struggle and resistance in the field of the profession, the National Policy of Practice (PNE) was collectively constructed, during the management of ABEPSS (2009-2010), with the aim of ensuring critical social direction in the training process. The policy was based on the Curricular Guidelines of ABEPSS of 1996, and its execution has demanded constant effort from the profession in the face of the conjunctural adversities of the Brazilian reality.